Classroom and subjective weavings (Educação e Pesquisa, 2008)
The objective of this article is to think the task of teaching under the focus of the vicissitudes to which the teacher-student relationship is subjected, which steer pupils and teachers away from the ideals of order and harmony. With the purpose of analyzing the intersubjective flows in the classroom, aspects of group psychodynamics are investigated with the use of the psychoanalytic notions of basic assumption group and of projective identification. With this procedure, we want at the same time to probe to which extent notions that are efficacious in psychoanalytic clinic can be useful to analyze and to understand situations that belong to the field of education, and in particular the classroom, seen here as a space for the production of psychic inter-occurrences. We try to think the intersubjective space according to a logic that considers the creation of a third party in teaching and learning. We introduce the notion of a "third voice" (Ogden) to denote the creation and re-creation of the intersubjective other with various effects on the subjective constitutions. The identitary stiffening, along with the attending disdain and intolerance to difference, can be a form of reacting to that which escapes from control and predictability, thereby weakening the transformational movements implicated in the process of learning.